Online Education in Family and Consumer Sciences University Programs and Four Models for Teaching Online. (18th February 2013) - Rehm, Marsha; Allison, Barbara N.; Bencomo, Angelina; Godfrey, Roxie V.
<x xml:space="preserve">Abstract</x> College and university faculty in Family and Consumer Sciences (FCS) programs are becoming more involved in online course design and instruction. The purpose of this article is twofold. First, examples of several existing FCS online programs are presented. Many online programs are being offered in the United States, and several are offered in an international setting (e.g. British Columbia, Saudi Arabia, and Thailand). Second, four models of education that FCS instructors can draw upon for teaching online are presented. The models are positivism, constructivism, the community of inquiry approach, and experiential learning. Positivism should be utilized when the goal is to teach specific and basic knowledge, which is usually contained in lectures and readings. Other models are more appropriate when the goal is to cultivate students' higher level thinking through dynamic learning processes. Constructivism is based on the assumption that learners are active creators of knowledge and meaning. The community of inquiry approach highlights the importance of building relationships for learning. The experiential learning model involves direct participation in realistic contexts and should be followed with reflection on the general principles of the learning situation. Online teaching strategies, examples, and limitations are presented for each model.